Derivatization and in situ metallation of phthalocyanines using click chemistry - Yilmaz, Yusuf; Sener, M. Kasim; Erden, Ibrahim; Avciata, Ulvi (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Dialkyl (3,4-dicyanophenyl)propargylmalonates were prepared by the reaction of propargyl bromide and the potassium salt of dialkyl-3,4-dicyanophenylmalonates. A cyclotetramerization reaction was achieved in pentanol in the presence of DBU without protective/deprotective chemistry, affording the peripherally tetrasubstituted alkynyl phthalocyanines. Subsequently, in situ metallation and 'clicking' were employed for the first time as an efficient and quantitative route to tetratriazole-functionalized phthalocyanines. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Click chemistry; Phthalocyanine; Supramolecular association; Metallation; NANOCRYSTALLINE TIO2 FILMS; SOLUBLE PHTHALOCYANINES; ZINC PHTHALOCYANINES; EFFICIENT; WATER; SENSITIZATION; COMPLEXES; THERAPY; COBALT; ROUTE; Chemistry; Crystallography